Protective Effect of Raf-1 Kinase Inhibitory Protein on Diabetic Retinal Neurodegeneration through P38-MAPK Pathway - Wu, Chuanling; Xu, Kai; Liu, Wenqiang; Liu, Anqi; Liang, Huimin; Li, Qunwang; Feng, Zhen; Yang, Yang; Ding, Jiayuan; Zhang, Tianyi; Liu, Yingxue; Liu, Xuezheng; et al. (Current eye research, 2022)
This study aimed to investigate the effect of Raf-1 kinase inhibitory protein (RKIP) on diabetic retinal neurodegeneration in streptozotocin-treated rat model and high glucose-treated rat Müller cells. Control and streptozotocin-treated rats were intravitreally injected with saline, RKIP gene overexpression lentivirus (oeRKIP) or negative control lentivirus (RKIP-vector). Normal or high glucose-treated Müller cells were transfected with saline, RKIP gene overexpression lentivirus or negative control lentivirus. Western blotting and immunofluorescence assay were utilized to evaluate the function of RKIP on the expression of RKIP, p38 mitogen-activated protein kinase (p38-MAPK), glutamate/aspartate transporter (GLAST), glutamine synthetase (GS), glial fibrillar acidic protein (GFAP) and cysteine-aspartic acid protease-3 (caspase-3). A glutamate assay kit was adopted to detect glutamate level in retina samples. Apoptosis of Müller cells was determined by Annexin-V/PI staining and flow cytometry. High glucose-treated Müller cells exhibited promoted apoptosis, while RKIP overexpression in high glucose-treated Müller cells down-regulated the enhanced apoptosis. Compared with rats injected with saline, streptozotocin-treated hyperglycemic rats displayed enhancement in the immunoreactivities of p38-MAPK and GFAP as well as in the protein expression of p38-MAPK and caspase-3. Strikingly, intravitreal injection of RKIP gene overexpression lentivirus in the hyperglycemic rats reversed the augmented immunoreactivities and protein expression mentioned above. Meanwhile, RKIP overexpression in the hyperglycemic rats improved the immunoreactivities and protein expression of RKIP, GS and GLAST. Besides, RKIP down-regulated the increased level of retinal glutamate in the hyperglycemic rats. Intravitreal injection of RKIP gene overexpression lentivirus functioned in preventing diabetic retinal neurodegeneration in a rat model of diabetes presumably by inhibiting p38-MAPK pathway.